(untitled) (Microbes and Health, 2013)
The study was conducted to investigate the efficacy of Baby chick Ranikhet Disease Vaccine (BCRDV) and Ranikhet Disease Vaccine (RDV) produced by the Livestock Research Institute (LRI), Mohakhali, Dhaka. For this experiment, 100 day-old-chick was purchased from Phinex Hatchery Ltd., Gazipur. The chicks (n=100) were divided into two groups. In group A (n=50), vaccination was performed twice with BCRDV at 2 and 21 days of age through intraocular route (i/o) followed by once with RDV at 60-day of age through intramuscular (i/m) route. Group B (n=50) was kept as unvaccinated control. The immunogenicity of the vaccine was evaluated by measuring the serum HI antibody titers at 1-, 20-, 36-, and 76-day of age, while the vaccine efficacy was examined by a challenge infection experiment with a velogenic field isolate of NDV as well as passive protection test. It was observed that the maternal antibody titers of the unvaccinated control group B gradually declined from day 1 to day 76 of age. Conversely, after primary and secondary vaccination with BCRDV, the levels of serum HI titer slightly increased in vaccinated group A compared with those in control group B. Finally administration of RDV resulted in a sharp increase in HI titer, leading to protection from challenge infection with virulent field virus as well as passive protection test. These results clearly demonstrated that a prime-booster immunization with BCRDV and RDV, both produced by LRI, is effective to protect chicken against Newcastle disease (ND). DOI: http://dx.doi.org/10.3329/mh.v1i1.13706 Microbes and Health Vol.1(1) June 2012 pp.9-13